2019
DOI: 10.1088/1741-4326/ab4248
|View full text |Cite
|
Sign up to set email alerts
|

Density peaking in JET—determined by fuelling or transport?

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 37 publications
4
49
1
Order By: Relevance
“…Therefore, although this kind of ICRH-NBI identity pulse pair cannot be performed in JET high power conditions due to lack of the required ICRH power, the significant role played by the NBI fueling in contributing to density peaking seems very much plausible. There is in fact evidence on that, reported in reference [12] based on density peaking in the JET three-point dimensionless collisionality scan. However, there is also evidence that as the ITG turbulence is less dominant or in other words when TEM dominates, the role of NBI fueling in contributing to density peaking tends to decrease which have been published in references [13,14].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, although this kind of ICRH-NBI identity pulse pair cannot be performed in JET high power conditions due to lack of the required ICRH power, the significant role played by the NBI fueling in contributing to density peaking seems very much plausible. There is in fact evidence on that, reported in reference [12] based on density peaking in the JET three-point dimensionless collisionality scan. However, there is also evidence that as the ITG turbulence is less dominant or in other words when TEM dominates, the role of NBI fueling in contributing to density peaking tends to decrease which have been published in references [13,14].…”
Section: Discussionmentioning
confidence: 76%
“…These observations suggest that the conclusions of this work remain valid for reactors. Isotope profiles tied to electron profiles regardless of core isotope source, fast isotope-mixing, and electron density peaking dominated by transport (due to large D e [13]), can all co-exist in a reactor relevant regime. This work directly follows from experimental [18] and theoretical [23] observation of large ion particle transport coefficients for ITG dominated plasmas.…”
Section: Sensitivitiesmentioning
confidence: 99%
“…Also, it is clear that the density peaking of the deuterium plasma is lower than for the hydrogen plasma, however this could be related to the lower density pedestal leading to increased core beam fuelling. Density peaking due to core sources and transport has been the subject of many studies and the relative contribution remains uncertain, requiring further investigation and more experiments [27], [28], [29] . Modelling has shown that there is a weak effect of isotope mass on density peaking but this was in plasmas without NBI heating, so there was no central source of particles [30].…”
Section: Isotope Exchangementioning
confidence: 99%